Deixis mitigation strategies - Melnik Olga Gennadievna (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2016)
The article analyses the deictic mitigation as a special type of mitigation devices directed at distancing the speaker from the content of the utterance. In most cases, the point of reference coincides with the speaker. It is well known that the main types of deixis are person, place and time. It was found out that the deixis of place does not play a significant role in the expression of the mitigation strategy. The research has revealed that reference to both the time and the person coordinates of the deictic center plays an important part in the development of mitigating strategies. The main distancing strategy with the help of the time deixis is the usage of conditional forms of verbs. In addition to mitigating strategy underlying deictic shift along the temporal coordinate the speakers could use metaphoric shift along the coordinates of the speech act. It was proved that the deletion of the speech act participants’ identity (the indefinite pronoun one, the agentless passive construction, and the pseudo-inclusive pronoun we.) one can get the mitigating effect. The partial deictic shift from the speaker’s coordinate towards the listener brings about a particular perlocutionary effect: it diminishes the speaker’s role. The authors come to a conclusion about the necessity of highlighting the mitigating function of deixis, which is a kind of Deixis ad Phantasma but not as the secondary, narrative deixis but as the primary dialogue deixis referring to the information implied in the utterance.